Pengaruh Kekayaan Daerah dan Belanja Modal Terhadap Kinerja Penyelanggaraan Pemerintah: Pengujian Legislative Power Sebagai Variabel Pemoderasi - Usman, Regina; Misra, Fauzan; Firdaus, Firdaus (E-Jurnal Akuntansi, 2019)
In addition, this study also aims to see how the legislative power variable can strengthen the relationship between regional wealth variables and capital expenditure on the performance of local government operations. The criteria for collecting sampling in this study were using purposive sampling techniques to obtain a sample of 149 provinces for five years. This study used a multiple linear regression analysis models with the Moderate Regression Analysis method. The results of the study indicated that the regional wealth variable did not affect the performance of regional government administration, while capital expenditure had a positive and significant effect on the performance of local government operations. The results also showed that legislative power could weaken the relationship between capital expenditure and the performance of local government operations . Keywords : Regional Wealth; Capital Expenditures;  Legislative Power; Performance of Local Government Operation.